2006
DOI: 10.1093/ajcn/83.5.993
|View full text |Cite
|
Sign up to set email alerts
|

Folate and human reproduction

Abstract: The influence of folate nutritional status on various pregnancy outcomes has long been recognized. Studies conducted in the 1950s and 1960s led to the recognition of prenatal folic acid supplementation as a means to prevent pregnancy-induced megaloblastic anemia. In the 1990s, the utility of periconceptional folic acid supplementation and folic acid food fortification emerged when they were proven to prevent the occurrence of neural tube defects. These distinctively different uses of folic acid may well be ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
325
1
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(346 citation statements)
references
References 396 publications
(402 reference statements)
7
325
1
13
Order By: Relevance
“…160 Folate is a vitamin that is essential for reproductive health, and a well known prenatal supplement. 152 Choline levels were equal in placenta from preeclamptic and normotensive pregnancies (paper III), suggesting a compensatory e ect on placental choline levels by increasing cell membrane catabolism. Comparing severe with non-severe preeclampsia, an additional increase in choline was found in tissue from the severe group (paper III).…”
Section: Placental Metabolism In Active Preeclampsiamentioning
confidence: 95%
See 1 more Smart Citation
“…160 Folate is a vitamin that is essential for reproductive health, and a well known prenatal supplement. 152 Choline levels were equal in placenta from preeclamptic and normotensive pregnancies (paper III), suggesting a compensatory e ect on placental choline levels by increasing cell membrane catabolism. Comparing severe with non-severe preeclampsia, an additional increase in choline was found in tissue from the severe group (paper III).…”
Section: Placental Metabolism In Active Preeclampsiamentioning
confidence: 95%
“…Indeed, plasma homocysteine is not elevated before clinical signs of preeclampsia, but increases once the signs develop. 152 Similarly, the decrease in urinary p-cresol sulfate for women with preeclampsia (paper I) was not re ected in early pregnancy (paper II). This metabolite is a gut microbial byproduct, 154 and a uremic retention solute which has shown proinammatory e ects on endothelium and kidney cells, and may induce shedding of endothelial microparticles.…”
mentioning
confidence: 92%
“…Adequate folate status is important not only during the periconceptional period, but also throughout pregnancy to achieve a satisfactory pregnancy outcome [1]. Since unambiguous evidence has shown that folic acid protects against both the first occurrence and the recurrence of neural tube defects [2,3], expert committees worldwide have issued folic acid recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease), hypothyroidism, birth defects and late pregnancy complications, such as preeclampsia, intrauterine grow retardation, preterm birth and intrauterine fetal death and abruption of placenta [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%